Jihad and just war in the war on terror - Brahimi, Alia. (Oxford : Oxford University Press, 2010)
This text explores the cases for war put forward by George W. Bush and Osama bin Laden. It systematically lays out how violence has been justified on both 'sides', and how these justifications have been criticized within the West and the Muslim world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Just war doctrine; Jihad; War on Terrorism, 2001-2009.; War -- Religious aspects -- Christianity; War -- Religious aspects -- Islam